Autonomous and Intelligent Systems Third International Conference, AIS 2012, Aveiro, Portugal, June 25-27, 2012. Proceedings - Kamel, Mohamed; Karray, Fakhri; Hagras, Hani.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Third International Conference on Autonomous and Intelligent Systems, AIS 2012, held in Aveiro, Portugal, in June 2012, collocated with the International Conference on Image Analysis and Recognition, IACIAR 2012. The 31 revised full papers were carefully reviewed and selected from 48 submissions. The papers are organized in topical sections on autonomous sensors and sensor systems, autonomous systems and intelligent control with applications, intelligent fuzzy systems, intelligent robotics, intelligent knowledge management, swarm and evolutionary methods, and applications
Keywords: Computer science; Computer Communication Networks; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; Image Processing and Computer Vision; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery